1988
DOI: 10.1021/jf00084a037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing on the phytic acid content of Bengal grams (Cicer arietinum) products

Abstract: Varsel, C. "Citrus Juice Processing as Related to Quality and Nutrition". In Citrus Nutrition and Quality; Nagy, S., Attaway,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…Phytate, the major phosphorous-bearing compound in cereals and pulses chelates divalent cations like iron, forming insoluble complex and thereby decreasing the iron bioavailability in humans (Vohra et al, 1985; Morris & Ellis, 1980). The decrease in phytic acid content, possibly through its destruction on roasting, may indicate that the divalent cations are freed from the phytate mineral complex which may account for the improved availability of iron in roasted weaning foods (Khan et al, 1988). Reduction in iron availability by the presence of phytate has been reported in rice, wheat, ragi, sorghum, bajra, red gram, bengal grain, green gram and amaranth (Murthy eta]., 1985;Hazel1 &Johnson, 1987).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Phytate, the major phosphorous-bearing compound in cereals and pulses chelates divalent cations like iron, forming insoluble complex and thereby decreasing the iron bioavailability in humans (Vohra et al, 1985; Morris & Ellis, 1980). The decrease in phytic acid content, possibly through its destruction on roasting, may indicate that the divalent cations are freed from the phytate mineral complex which may account for the improved availability of iron in roasted weaning foods (Khan et al, 1988). Reduction in iron availability by the presence of phytate has been reported in rice, wheat, ragi, sorghum, bajra, red gram, bengal grain, green gram and amaranth (Murthy eta]., 1985;Hazel1 &Johnson, 1987).…”
Section: Discussionsupporting
confidence: 63%
“…Roasting imparts a porous structure to the grain while giving it aroma and flavour (Yasoda Devi & Geervani, 1983). Lowering the concentration of antinutrients may be responsible for increasing their protein and starch digestibility and iron availability (Singh, 1984;Bjorck et al, 1987;Khan et al, 1988). The effect of processing on starch and protein digestibility and iron availability was investigated.…”
Section: Cereals and Pulses Constitute An Importantmentioning
confidence: 99%
“…Bishnoi et al (1994) found an 8% decrease of PHYTATE in peas by ordinary cooking and 12% by pressure cooking. Boiling of white and brown Bengal grams as practiced in Pakistan resulted in 25% loss of PHYTATE (Khan et al, 1988). We found about 15% less in cooked chickpeas and lentils (Table 1).…”
Section: Resultsmentioning
confidence: 70%
“…Bishnoi et al (1994) reported vegetable peas in India to contain 9.5 to 9.9 mmol/kg of PHYTATE and field peas contained 11.5 to 11.8 mmol/kg. Raw Pakistani lentils contained 9.4 mmol/kg of PHYTATE (Manan et al, 1987) and brown and white Bengal grams contained 18.5 and 12.1 mmol/kg (Khan et al, 1988). Mature black beans contained 19.3 mmol/kg of PHYTATE before storage (Sievwright and Shipe, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, low temperature drying yields greater activity of enzymes in grains, while high temperature drying operations lead to the inactivation of destructive enzymes and to the reduction of antinutritional factors, which improves the storage and nutritional quality of the product (D'Appolonia ; Khan et al . ; Gahlawat and Sehgal ; Griffith and Castell‐Perez ).…”
Section: Introductionmentioning
confidence: 99%